Top management challenges and concerns for agronomic crop production in California: Identifying critical issues for extension through needs assessment. (8th November 2021) - Kanter, Jessica; Clark, Nicholas; Lundy, Mark Edward; Koundinya, Vikram; Leinfelder‐Miles, Michelle; Long, Rachael; Light, Sarah E.; Brim‐DeForest, Whitney B.; Linquist, Bruce; Putnam, Dan; Hutmacher, Robert B.; Pittelkow, Cameron M.
Abstract: Agronomic cropping systems in many regions face growing economic and management challenges as well as new regulations designed to address negative environmental and social externalities. At the same time, public support for agricultural education and extension is decreasing. Hence, new approaches are necessary to understand the most pressing on‐farm issues and help prioritize critical needs. With a diversity of agronomic crops and new regulations for water and nitrogen, California is an important case study for other regions. The objective of this study was to identify major grower and industry concerns, management challenges, and motivations in making management decisions. In 2020, 483 growers, consultants, and allied industry of agronomic crop production responded to an online survey. The crops most widely grown by respondents included rice ( Oryza sativa L.), alfalfa ( Medicago sativa L.), wheat ( Triticum aestivum L.), and corn ( Zea mays L.). Four out of the five top concerns were related to water. Weed control and irrigation/water management were primary management challenges, though differences occurred by crop and region. The highest priorities considered in grower management decision‐making were water, profitability, and land stewardship. Crop rotation benefits were a primary reason for growing agronomic crops, with profitability and tradition ranking closely behind. This study highlights opportunities to guide research and extension efforts based on critical needs identified by growers and industry, while also informing larger policy and institutional decisions regarding new programs and funding to address key issues in agronomic crop production. Core Ideas: Water‐related issues are of greatest concern while weed control is top challenge for agronomic crops in California. Availability of water, profitability, and land stewardship were the highest priorities in management decisions. Crop rotation benefits and profitability were the primary reasons for growing agronomic crops. Extension must balance immediate needs with long‐term education to adapt to future challenges.